2014
DOI: 10.4103/0970-0218.137155
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of under 5 children belonging to tribal population living in riverine (Char) areas of Dibrugarh district, Assam

Abstract: Context:Assam's main lifeline, the Brahmaputra river, braided nature created numerous sand bars and islands known as chars/sapories. They are home to more than 3 million people. Over 90% of the cultivated land on the river islands is flood-prone; the flood leaves the islands completely separated from mainland, preventing access to health infrastructure and services. Aims: To assess the nutritional status of under 5 children residing in the char areas of Dibrugarh district and to identify the factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 6 publications
9
59
4
Order By: Relevance
“…Similar findings were observed by other studies conducted by Sukla P et al [20] at Chhattisgarh, Mamulwar MS et al [21] in Pune and Islam S et al [22] in a tribal area of Dibrugarh district of Assam which found the prevalence rate of underweight between 29.00% to 36.00% respectively. While in contrast, the study done by Radhamani KV et al [23] showed the prevalence rate of underweight as 14.60% at North Kerala.…”
Section: Original Research Articlesupporting
confidence: 89%
“…Similar findings were observed by other studies conducted by Sukla P et al [20] at Chhattisgarh, Mamulwar MS et al [21] in Pune and Islam S et al [22] in a tribal area of Dibrugarh district of Assam which found the prevalence rate of underweight between 29.00% to 36.00% respectively. While in contrast, the study done by Radhamani KV et al [23] showed the prevalence rate of underweight as 14.60% at North Kerala.…”
Section: Original Research Articlesupporting
confidence: 89%
“…Nayak RK et al (38.2%), Islam S et al (30.4%), Sapkota VP et al (37%) reported similar prevalence of stunting. [10][11][12] But it differed from prevalence of stunting in Maharashtra (44%) according to NFHS-3.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the preschool children require serious attention because it is the period of rapid physical growth and development, which increase the vulnerability of undernutrition in population (WHO 1995). Natural calamities like flood, affect the children health in a very adverse way with a continuous phenomenon and it severely effect on child nutritional status in Assam (Islam et al 2014). Assam's main lifeline is surrounded by various rivers and they cause catastrophic flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Assam's main lifeline is surrounded by various rivers and they cause catastrophic flooding. Over 90% of the cultivated land and villages are floodprone (Islam et al 2014). The flood leaves the villagers completely isolated from the mainland, thereby preventing access to health infrastructure and services.…”
Section: Introductionmentioning
confidence: 99%